1982
DOI: 10.1039/p29820001055
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanisms of nucleophilic displacements with heterocycles as leaving groups. Part 6. Reactions of N-(substituted benzyl)azaheterocyclonium compounds with piperidine

Abstract: The preparation is described of series of N-(p-substituted)benzyl and N-(2-furfuryl) compounds with different heterocyclic leaving groups. First-and second-order rate constants for their reactions with piperidine in chlorobenzene are measured and discussed. Plots of k2 values for substituted compounds versus k2 for the parent Nbenzyl derivative are linear for each substituent despite variable temperature of measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…separation conditions); the pbromobenzylpyridines (3) and (4a) were found, and also three more p-bromobenzylated isomers. Some 1,2-bis-(p-bromophenyl)ethane and a trace of a bis-(p-bromobenzyl) pyridine (7) were also detected.…”
Section: Monocyclicmentioning
confidence: 99%
See 1 more Smart Citation
“…separation conditions); the pbromobenzylpyridines (3) and (4a) were found, and also three more p-bromobenzylated isomers. Some 1,2-bis-(p-bromophenyl)ethane and a trace of a bis-(p-bromobenzyl) pyridine (7) were also detected.…”
Section: Monocyclicmentioning
confidence: 99%
“…Comparison of retention times with those obtained in the runs carried out in chloro-and nitro-benzene showed that the first and second isomers to be eluted were (3) and (4a), respectively. The least volatile detected component was again a trace of a bis-(p-bromobenzy1)pyridine(7) (M 641, 79Br/79Br) of unknown substitution pattern. Study of the material balance for the thermolysis of (1) neat at 250 "C showed that approximately 30% of the p-bromobenzyl group was accounted for in the form of the four isomeric C-(pbromobenzyl) derivatives (3) and (4) of the pyridine (2).Tricyclic Series.-1 -Benzyl-2-t-butyl-4-phenyl-5,6-dihydrobenzo[h]quinolinium tetrafluoroborate (9) on heating for 4 h in chlorobenzene at 100 "C gave the salt(8) together with one or more benzylchlorobenzenes, and a mixture of four benzylated 2-t-butyl-5,6-dihydro-4-phenylbenzo[h]quinolines (10) as shown by g.1.c.-mass spectrometry.…”
mentioning
confidence: 98%